Influence of laser parameters on superhydrophobicity- A review. (23rd April 2021) - Raja, R Samuel Sanjay; Selvakumar, P; Babu, P Dinesh; Rubasingh, B Jacob; Suresh, K
Abstract: Superhydrophobicity is also known as lotus effect which makes the water to roll off and bounce when liquid droplets resting on the surface. In nature it is used by plants for self-cleaning purpose and by animals for anti-adhesion skin. The superhydrophobic surface has been mimicked and used in the field of aerospace, textiles, power line, solar cell and so on. In this review we provide the basic theories of wetting, wetting transition models of superhydrophobicity, parameters of laser beam and post processing (heat treatment only) after laser irradiation related to contact angle. Laser parameters play a vital role in producing surface topography. The surface topography may be consists of ripples, dual surface roughness on the laser textured surface. Based on the magnitude of laser parameters the different surface morphology can be obtained. The surface morphology will vary for the different laser system such femto, pico or nano second laser system. The present review aims to report the understanding of laser parameters in order to texture the expected surface structure by controlling the laser parameters.